Online Privacy Breaches, Offline Consequences: Construction and Validation of the Concerns with the Protection of Informational Privacy Scale. Issue 19 (25th November 2020) - Durnell, Eric; Okabe-Miyamoto, Karynna; Howell, Ryan T.; Zizi, Martin
ABSTRACT: Concerns with protecting privacy, especially of online data, has been a goal of privacy scholarship for years. Because most data are transferred online, many instruments focus on online environments. However, when privacy is invaded and data mishandled, the consequences, including the emotional ramifications, extend beyond the online space and into the offline world. Thus, we developed the CPIP, a measure of privacy concern. We were able to (1) determine the top four domains for informational privacy and (2) correlate that concern with emotional outcomes showing people with high concerns felt less calm, less at ease, and angrier, after reading prompts about the right to privacy protection. The CPIP predicts who experiences an emotional reaction to a loss of privacy and steps for Internet providers collecting data online to create a better balance for users and their privacy. This alignment (or misalignment) of attitudes and behaviors challenge the privacy paradox.